Differences Between Infectious Disease Events in First Liver Transplant Versus Retransplantation in the Swiss Transplant Cohort Study. Issue 9 (31st July 2021) - Kusejko, Katharina; Neofytos, Dionysios; Hirsch, Hans H.; Meylan, Pascal; Boggian, Katia; Hirzel, Cedric; Garzoni, Christian; Kouyos, Roger D.; Mueller, Nicolas J.; Schreiber, Peter W.
Abstract : Retransplantation after graft failure is increasingly performed, and inferior graft survival, patient survival, and quality of life has been reported. The role of infectious disease (ID) events in this less favorable outcome is unknown. We analyzed ID events after first liver transplantation (FLTpx) and retransplantation (reLTpx) in the Swiss Transplant Cohort Study. Clinical factors were compared after FLTpx and reLTpx, and survival analysis was applied to compare the time to ID events after FLTpx and after reLTpx, adjusted for age, sex, Model for End‐Stage Liver Disease score, donor type, liver transplant type (whole versus split liver), and duration of transplant surgery. In total, 60 patients were included (65.0% male, median age of 56 years). Overall, 343 ID events were observed: 204 (59.5%) after the FLTpx and 139 (40.5%) after reLTpx. Bacterial infections were most frequent (193/343, 56.3%), followed by viral (43/343, 12.5%) and fungal (28/343, 8.2%) infections, with less infections by Candida spp. but more by Aspergillus spp. after reLTpx ( P = 0.01). The most frequent infection site was bloodstream infection (86, 21.3%), followed by liver and biliary tract (83, 20.5%) and intraabdominal (63, 15.6%) infections. After reLTpx, more respiratory tract and surgical site infections were observed ( P < 0.001). The time to first infection was shorter after FLTpx (adjusted hazard ratio [HR], 0.5; 95%‐confidence interval [CI], 0.3‐1.0; P = 0.04). Reduced hazards for ID events after reLTpx were also observed when modelling recurrent events (adjusted HR, 0.5; CI, 0.3‐0.8; P = 0.003). The number of infections was comparable after FLTpx and reLTpx; however, differences regarding infection sites and fungal species were observed. Hazards were reduced for infection after reLTpx.